Atatürk's Understanding of Complete Independence in Building the Republic - Dogan, Zafer (Osman Kose, 2023)
This study aims to look at Atat & uuml;rk's understanding of complete independence in our republican history. In doing so, we will try to explain what the dependency relations inherited from the Ottoman Empire are (the Millet system, capitulations, etc.) Aand how we abolished them. The basic principle of Atat & uuml;rk's policy in the Republican era was based on independence and a relationship with other states based on equality. The Allies wanted to continue their traditional policy on the Eastern Question but Turkey rejected the old order based on all kinds of economic, political and legal privileges. Atat & uuml;rk tried to make Turkey an independent country, not only in economics and foreign policy, but also in education and culture. Of course, this attitude was closely related to the lessons and experiences he had learned from the collapsed empire. In this context, we believe that an objective assessment of the republic's complete independence will serve to better understand the republic's 100-year history.
Keywords: Complete Independence; Atat & uuml; rk; Economic and Political Independence; Capitulations; Language and Cultural Policies; History